1997
DOI: 10.1128/jvi.71.11.8307-8315.1997
|View full text |Cite
|
Sign up to set email alerts
|

The null mutant of the U(L)31 gene of herpes simplex virus 1: construction and phenotype in infected cells

Abstract: Earlier studies have shown that the U L 31 protein is homogeneously distributed throughout the nucleus and cofractionates with nuclear matrix. We report the construction from an appropriate cosmid library a deletion mutant which replicates in rabbit skin cells carrying the U L 31 gene under a late (␥ 1 ) viral promoter. The mutant virus exhibits cytopathic effects and yields 0.01 to 0.1% of the yield of wild-type parent virus in noncomplementing cells but amounts of virus 10-to 1,000-fold higher than those rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 33 publications
2
43
0
2
Order By: Relevance
“…This complex recruits viral and cellular kinases, such as US3 or UL13, and protein kinase C (PKC) to phosphorylate and soften the nuclear lamina, subsequently allowing nucleocapsids to access the INM 31,41 . UL31 or UL34 deletion blocked virion nuclear egress, and all nucleocapsids accumulated in the nucleus 42,43 . Although UL47 deletion also blocks virion nuclear egress, the researchers suggested that UL47 protein played a regulatory role only in nucleocapsid nuclear egress 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This complex recruits viral and cellular kinases, such as US3 or UL13, and protein kinase C (PKC) to phosphorylate and soften the nuclear lamina, subsequently allowing nucleocapsids to access the INM 31,41 . UL31 or UL34 deletion blocked virion nuclear egress, and all nucleocapsids accumulated in the nucleus 42,43 . Although UL47 deletion also blocks virion nuclear egress, the researchers suggested that UL47 protein played a regulatory role only in nucleocapsid nuclear egress 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This mode of nuclear escape has, however, only been observed after forced reversion analysis in cell culture. Differing roles for pUL31 and pUL34 in nuclear egress have been demonstrated (7,8), including recruitment of viral and cellular kinases that locally disrupt the lamina (15)(16)(17)(18)(19) as well as functions in herpesvirus replication beyond nuclear egress, including viral DNA binding and packaging (44,45) or cell-to-cell spread (46).…”
Section: Discussionmentioning
confidence: 99%
“…To conduct a comprehensive analysis of ICP22/U S 1.5, it was necessary to construct a virus from which the entire open reading frame of ␣22/U S 1.5 had been deleted. To delete the entire ␣22/U S 1.5 domain, we used a modified cosmid system as described previously (7,12) and in Materials and Methods. This cosmid set is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cosmids. The set of cosmids used in this study was derived from HSV-1(F) DNA as described elsewhere (7,12) and is illustrated in Fig. 1A, lines 2 through 6.…”
Section: Methodsmentioning
confidence: 99%